2008
DOI: 10.1902/jop.2008.070652
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy as an Adjunct to Non‐Surgical Periodontal Treatment: A Randomized, Controlled Clinical Trial

Abstract: The additional application of a single episode of PDT to scaling and root planing failed to result in an additional improvement in terms of PD reduction and CAL gain, but it resulted in a significantly higher reduction in bleeding scores compared to scaling and root planing alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
145
5
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(190 citation statements)
references
References 29 publications
(43 reference statements)
18
145
5
22
Order By: Relevance
“…14 In another clinical trial that was conducted in 2008 by Christodoulides et al, 24 patients with chronic periodontitis were randomly divided into 2 groups: 1-treatment with SRP, 2-treatment with SRP and PDT (diode laser 670 nm and power of 75 mW) and no statistically significant difference was seen between the 2 groups, and only BOP showed significant improvements in the group treated with SRP and PDT, compared to the one treated with SRP alone. 15 In another clinical trial conducted in 2009 by Chondros et al, 24 patients with chronic periodontitis were divided into 2 groups: group 1-treatment by SRP and group 2-treatment with SRP and PDT (670 nm, 75 mW laser diode and photosensitizer phenothiazine chloride for 60 seconds), respectively. Both groups were assessed at 2 time periods of 3 and 6 months.…”
Section: Review Of Literaturementioning
confidence: 99%
“…14 In another clinical trial that was conducted in 2008 by Christodoulides et al, 24 patients with chronic periodontitis were randomly divided into 2 groups: 1-treatment with SRP, 2-treatment with SRP and PDT (diode laser 670 nm and power of 75 mW) and no statistically significant difference was seen between the 2 groups, and only BOP showed significant improvements in the group treated with SRP and PDT, compared to the one treated with SRP alone. 15 In another clinical trial conducted in 2009 by Chondros et al, 24 patients with chronic periodontitis were divided into 2 groups: group 1-treatment by SRP and group 2-treatment with SRP and PDT (670 nm, 75 mW laser diode and photosensitizer phenothiazine chloride for 60 seconds), respectively. Both groups were assessed at 2 time periods of 3 and 6 months.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers. 22,26,28,31,32 Changes of microbiological parameters were evaluated in 8 of 18 studies.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers. 22,26,28,31,32 Changes of microbiological parameters were evaluated in 8 of 18 studies. Four studies have found a statistically significant effect of the additional use of PDT on the reduction of periodontal pathogens, 28,35,37,38 while 4 studies have failed to reveal any differences between the treatments groups.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the differences among the studies were obvious, with two studies with a clear impact in both variables 1,2 , and two studies (those performed by the same group) with smaller impact and minor differences among groups. 3,4 The first two studies had a 12-week follow up, while the last two had a 24-week duration, although the 12-week results were included in the meta-analysis. In addition, one of last two studies included patients in supportive periodontal therapy (already treated and following a secondary prevention program), despite the inclusion criterion of the review of 'untreated chronic periodontitis'.…”
mentioning
confidence: 99%